Optimal concentration of Lugol's solution for detecting early esophageal carcinoma: A randomized controlled trial - Qu, Jun‐yan; Li, Yan; Liu, Guan‐qun; Li, Zhen; Zhong, Ning; Zhang, Ming‐ming; Li, Yue‐yue; Yu, Tao; Lu, Xue‐feng; Li, Li‐xiang; Liu, Han; Qi, Qing‐qing; et al. (Journal of gastroenterology and hepatology, 2023)
Background and Aim Lugol chromoendoscopy is the standard technique to detect an esophageal squamous cell carcinoma (ESCC). However, a high concentration of Lugol's solution can induce mucosal injury and adverse events. We aimed to investigate the optimal concentration of Lugol's solution to reduce mucosal injury and adverse events without degrading image quality. Methods This was a two‐phase double‐blind randomized controlled trial. In phase I, 200 eligible patients underwent esophagogastroduodenoscopy and then were randomly (1:1:1:1:1) sprayed with 1.2%, 1.0%, 0.8%, 0.6%, or 0.4% Lugol's solution. Image quality, gastric mucosal injury, adverse events, and operation satisfaction were compared to investigate the minimal effective concentration. In phase II, 42 cases of endoscopic mucosectomy for early ESCC were included. The patients were randomly assigned (1:1) to the minimal effective (0.6%) or conventional (1.2%) concentration of Lugol's solution for further comparison of the effectiveness. Results In phase I, the gastric mucosal injury was significantly reduced in 0.6% group (P < 0.05). Furthermore, there was no statistical significance in image quality between 0.6% and higher concentrations of Lugol's solution (P > 0.05, respectively). It also showed that the operation satisfaction decreased in 1.2% group compared with the lower concentration groups (P < 0.05). In phase II, the complete resection rate was 100% in both groups, while 0.6% Lugol's solution showed higher operation satisfaction (W = 554.500, P = 0.005). Conclusions The study indicates that 0.6% might be the optimal concentration of Lugol's solution for early detection and delineation of ESCC, considering minimal mucosal injury and satisfied image. The registry of clinical trials: ClinicalTrials.gov (NCT03180944).